(untitled) (New Jersey, 2005)
This book was the first to thoroughly integrate the use of Microsoft Excel as a tool for statistical analysis. The book focuses on the concepts of statistics with applications to the functional areas of business. It is rich in applications from accounting, finance, marketing, management and economics, covering data collection, tables and charts, probability, estimation, and more. For professionals, particularly managers, making financial analyses and decisions.
Keywords: Microsoft excel (computer file),Management,Commercial statistics,Electronic spreadsheets; Statistical methods